THE EFFECT OF HEDONIC MOTIVATION AND VISUAL MERCHANDISING ON IMPULSE BUYING WITH POSITIVE EMOTION AS A MEDIATION VARIABLE ON OH SOME STORE CONSUMERS IN SAMARINDA CITY - Nirmala Putri Dinanti; Gusti Noorlitaria Achmad (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to analyze the influence of hedonic motivation and visual merchandising on impulse buying with positive emotion as a mediating variable among OH SOME Store consumers in Samarinda City. The study used a quantitative approach with a purposive sampling technique on 136 respondents who had shopped at OH SOME Store Samarinda. Data collection was conducted through a questionnaire using a Likert scale and analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The results showed that hedonic motivation had a positive and significant effect on impulse buying and positive emotion. Positive emotion was also proven to have a positive and significant effect on impulse buying. Meanwhile, visual merchandising did not have a significant direct effect on impulse buying, but had a positive and significant effect on positive emotion. In addition, positive emotion was able to mediate the influence of hedonic motivation and visual merchandising on impulse buying. The implications of this study indicate that retail companies need to create a pleasant shopping experience by strengthening consumers' emotional aspects, developing attractive store visual concepts, and experiential marketing strategies to increase consumer impulse buying.